Prevalence and Prognostic Impact of Apical Sparing Contractility Pattern in Patients with Aortic Stenosis Referred for Transcatheter Aortic Valve Implantation - Ferreira, V (2022)
Introduction: Prolonged afterload increase in aortic stenosis (AS) may alter left ventricular (LV) contractility, irrespective of LV ejection fraction (LVEF). The prevalence and morbimortality associated with the apical sparing strain pattern (ASP), a typical finding of cardiac amyloidosis (CA), are not fully understood in patients with AS. We assessed the prevalence of the ASP in patients with severe AS and its clinical impact after transcatheter aortic valve implantation (TAVI). Methods: Eighty-nine consecutive patients with severe AS and LV hypertrophy referred for TAVI were included. Baseline clinical and echocardiographic data were assessed, including the ASP in bull's eye plots (ASPB), relative apical longitudinal strain (RALS) and EF to global longitudinal strain (EF/GLS) ratio. We analysed all-cause mortality; a composite of all-cause mortality, stroke, and heart failure hospitalizations; and the rate of pacemaker implantation, after TAVI. Results: Mean age was 82 ± 6 years and mean LVEF was 57 ± 10%. ASPB and RALS >1 were present in 43.8% and 24.7% of patients, respectively. Over a median follow-up of 13 months (IQR 6-32), ASPB was associated with higher rates of all-cause mortality (log-rank P=0.001) and was an independent predictor of all-cause mortality in multivariate analysis. Combination of the ASPB and GLS or EF/GLS ratio improved the risk stratification. Patients with RALS >1 were more likely to have new BBB and an indication for pacemaker implantation (P=0.048). Conclusion: The ASP, as assessed by the ASPB and RALS, was frequent in patients with AS regardless of the diagnosis of CA. The ASPB may refine risk stratification in patients referred for TAVI.